IMPROVING EARLY CHILDREN'S SOCIAL COGNITIVE ABILITY THROUGH ART LEARNING IN TERNATE, NORTH MALUKU - Radjiman (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
This study aims to improve the social cognitive abilities developed by Bandura through art learning in early childhood. The research method uses action research developed by Lewin. Data collection techniques using observation sheets or observations. Data analysis techniques using t-test. The research sample of students was 30 children in group B. Cognitive abilities were not only developed by Piaget and Vygotsky, but also by Bandura. The cognitive theory developed by Bandura is known as social cognitive because it emphasizes more on the process of modeling and imitating to acquire knowledge. Early childhood cognitive development can be done through various methods and techniques as well as learning materials and resources. Art ability is developed in every curriculum in early childhood. The results showed that the end of the cycle obtained data t-count 3.98> t-table 1.697 at a significance level of 0.05. Thus it can be concluded that social cognitive abilities through art learning are effectively used. It is suggested, to improve social cognitive abilities can be done through art learning.